A Bibliometric Analysis of South Korean TV Dramas from 2014 to 2023 in the WoS Database - Dang , Lixia; Ahmad, Abdul Latiff Bin; Hashim, Hasrul (Journal of Ecohumanism, 2024)
South Korean TV dramas (K-dramas, hereafter) have deeply captivated a worldwide audience for a long time. However, there have been few bibliometric studies specifically addressing this topic. The aim of this study is to conduct a bibliometric analysis of research on K-dramas. A total of 137 English-language journal articles were collected. This research used analytical tools such as Biblioshiny with R packages and the VOS viewer. The findings show that, South Korea, the United States (USA), and China are the top countries in terms of research production in the field of K-dramas. The analysis of four keyword clusters estimates future trends. Firstly, K-dramas on the Netflix platform have the potential to become a research trend in the future. Moreover, it is necessary to analyse the relationship between South Korean culture and other cultures. The concept of cultural hybridity can be applied to elaborate the contemporary global spread of K-dramas. Furthermore, it is essential to allocate greater focus to the fandom and youth groups. Finally, it is crucial to pay attention to the portrayal of gender characteristics, specifically masculinity, in K-dramas. The article concludes by listing the research’s limitations.